Factors influencing generation Y investors when choosing a broker firm - Pipatvanit, Kamonchanok (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Abstract This research examined the factors influencing generation Y investors when choosing a broker firm of generation Y in Bangkok. The researcher used the multiple linear regression and the Pearson correlation coefficient for statistical tests to test the relationship and differences between dependent and independent variables. Therefore, the research used questionnaires to collect data from generation Y investors. A total of 290 generation Y investors were collected as the sample of the study. There are two variables considered, the dependent variable is generation Y investor’s decision and the independent variables are credibility, reliability, understanding clients, scale of the firm, and service offers. The results of Multiple linear regression analysis showed that these four factors, credibility, reliability, understanding clients, service offers has a statistically significant influence towards generation Y investor’s decision. They are indicated that credibility, reliability, and understanding of clients are significant whereas scale of the firm is not significant. Lastly, the results of Pearson correlation coefficient showed that there is a statistically significant correlation between these four factors, credibility, reliability, understanding clients, scale of the firm and selecting a brokerage. Then, there is a relationship between and selecting a brokerage firm. However, there is no relationship between scale of the firm and selecting a brokerage firm. Keywords: Generation Y, Brokers, Factors, Influence, Investor’s decision